Of Conflict in Virtual Learning Communities in the Context of a Democratic Pedagogy: A paradox or sophism? - Ozturk, Hayriye Tugba; Simsek, Omer (Proceedings of the International Conference on Networked Learning, 2012)
Conflict is a dynamic and complex concept which takes a crucial part in students' learning experiences, especially in learning communities underpinned with democratic pedagogy. Democratic pedagogies provide a base for emancipatory education by enabling students to participate in governance of their learning processes and so take responsibility for their own learning. In VLCs underpinned with democratic pedagogy, the method and content of the learning programme are not tightly structured in order to fulfil the community members' wishes, interests, ideas and so on, throughout the learning process. Within this framework, emergence of conflict among the community members is inevitable, given the diverse and sometimes clashing individual differences in participation in the negotiation process; in the loose structure of the programme which brings about uncertainty; and in the nature of the technological environments in which learning takes place. Once conflict emerges, it may lead to either an enjoyable or an unpleasant learning experience for students.Although in the literature it is identified as a negative or positive concept, in this research a neutral approach is taken to explore this concept holistically and openly. To surface the conflict in the learning process, a case study was conducted with third-year undergraduate students enrolled in a Computer Education and Instructional Technology programme in Turkey, during one academic term. In order to investigate students' experience with conflict in the context of democratic pedagogy, two learning groups were chosen: while the first group members did not perceive conflict, the second group members did experience severe conflict. By presenting these two contrasting groups' cases, it is aimed to exhibit the members' learning with and without conflict, and thereby to surface the importance of conflict in learning. Throughout the study, data was collected via interviews, focus group meetings, pre & post questionnaires, Moodle logs, and field notes. Data analysis was informed by grounded theory. Drawing on the findings, the dynamics and the roles of conflict in learning were discussed.We show how small groups of students in the community experienced different conflict pathways during the course of study. The findings demonstrate the importance of taking a holistic, processual view of the emergence of conflict in a learning community.